2022
DOI: 10.1136/jnis-2022-019510
|View full text |Cite
|
Sign up to set email alerts
|

Bridging thrombolysis improves survival rates at 90 days compared with direct mechanical thrombectomy alone in acute ischemic stroke due to basilar artery occlusion: a systematic review and meta-analysis of 1096 patients

Abstract: BackgroundMechanical thrombectomy (MT) is an effective treatment for patients with acute ischemic stroke (AIS) from basilar artery occlusion (BAO).ObjectiveTo compare the clinical outcomes of MT, with and without bridging intravenous thrombolysis (IVT), in acute BAO through a systematic review and meta-analysis of the current literature.MethodsSystematic searches of Medline, EMBASE, and Cochrane Central were undertaken on August 1, 2022. Good functional outcome defined as 90-day modified Rankin Scale score 0–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…In addition, the change in NIHSS could be explained by the significantly shorter interval between stroke symptom onset and puncture time in the IVT group and thus is most likely a selection bias. Previous studies reported a significantly longer interval between stroke symptom onset and puncture time in patients treated with EVT alone compared to IVT followed by thrombectomy as well (Siow et 13,19 Multiple regression models cannot fully account for the longer time interval between stroke onset and puncture in the EVT alone group, which might have influenced the outcomes and is a limitation of this study. Interestingly, Nie et al 18 reported an improved functional outcome in the IVT group despite the highest median onset ).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, the change in NIHSS could be explained by the significantly shorter interval between stroke symptom onset and puncture time in the IVT group and thus is most likely a selection bias. Previous studies reported a significantly longer interval between stroke symptom onset and puncture time in patients treated with EVT alone compared to IVT followed by thrombectomy as well (Siow et 13,19 Multiple regression models cannot fully account for the longer time interval between stroke onset and puncture in the EVT alone group, which might have influenced the outcomes and is a limitation of this study. Interestingly, Nie et al 18 reported an improved functional outcome in the IVT group despite the highest median onset ).…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies reported a significantly longer interval between stroke symptom onset and puncture time in patients treated with EVT alone compared to IVT followed by thrombectomy as well (Siow et al: 330 min vs. 240 min [mean] and Kohli et al: 711 min vs. 313 min [median]). 13,19 Multiple regression models cannot fully account for the longer time interval between stroke onset and puncture in the EVT alone group, which might have influenced the outcomes and is a limitation of this study. Interestingly, Nie et al 18 reported an improved functional outcome in the IVT group despite the highest median onset to puncture time of 510 min in the IVT group (IQR 378-763).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…45 With regard to bridging IVT, a recent meta-analysis concluded that patients with BAO had lower mortality and, in the case of large vessel atherosclerosis, also better functional outcome when they received IVT prior to EVT compared with direct EVT. 57 A pooled analysis of the EXTEND-IA TNK trial and the BATMAN registry compared tenecteplase and alteplase before EVT for BAO, revealing a higher pre-EVT recanalization rate with tenecteplase (26 vs. 7%) without an increase in the frequency of sICH. 58…”
Section: Recanalization Treatment-observational Studiesmentioning
confidence: 99%